A Scoping Review of Patient-Centered Perinatal Contraceptive Counseling. - Karlin, Jennifer; Newmark, Rebecca L.; Oberman, Nina; Dehlendorf, Christine (Maternal & Child Health Journal, 2024)
Introduction: Contraceptive counseling during the perinatal period is an important component of comprehensive perinatal care. We synthesized research about contraceptive counseling during the perinatal period, which has not previously been systematically compiled. Methods: We developed search criteria to identify articles listed in PubMed, Embase, and Popline databases published between 1992 and July 2022 that address patients' preferences for, and experiences of, perinatal contraceptive counseling, as well as health outcomes associated with this counseling. Search results were independently reviewed by multiple reviewers to assess relevance for the present review. Methods were conducted in accordance with PRISMA guidelines. Results: Thirty-four articles were included in the final full text review. Of the included articles, 10 included implementation and evaluation of a contraceptive counseling method or protocol, and 24 evaluated preferences for or experiences of existing contraceptive counseling in the perinatal period. Common themes included the acceptability of contraceptive counseling in the peripartum and postpartum periods, and a preference for contraceptive counseling at some point during the antenatal period and before the inpatient hospital experience, and direct provider-patient discussion instead of video or written material. Multiple studies suggest that timing, content, and modality should be individualized. In general, avoiding actual or perceived directiveness and providing multi-modal counseling that includes both written educational materials and patient-provider conversations was desired. Discussion: The perinatal period constitutes a critical opportunity to provide contraceptive counseling that can support pregnant and postpartum people's management of their reproductive futures. The reviewed studies highlight the importance of patient-centered approach to providing this care, including flexibility of timing, content, and modality to accommodate individual preferences. Significance: Our scoping review confirms that patients are receptive to contraceptive counseling in the perinatal period, and that this counseling should be delivered in an individualized manner given the diversity of patient needs during pregnancy and postpartum. More research is required to implement protocols that are flexible and patient centered.